Expression, prognostic value and function of LMBR1L in gastric cancer - Song Liang; Chaosheng Zhang; Chuanjun Wang; Yongkang Liang; Xueyi Feng; Chuansi Wang; Pin Jiang; Shenwei Wu; Xiuming Lu (Molecular Genetics and Genomics, 2026)

Rainstorm‑driven highly chlorine‑reactive DOM increases disinfection byproduct risks in drinking water - Zhengdi Wu; Pin Wang; Yu Lei; Yayun Zhang; Zhimin Qiang; Wenhai Chu (Water Research, 2026)

Interfacial electron redistribution and tandem active sites enable enhanced nitrate to ammonia conversion in Zr-MOF/MoS2 heterostructures - Naveen Karuppusamy; Zi-Yan Zhan; Ruspika Sundaresan; Chun Hsien Wu; Pandiyarajan Anand; Jeyakumar Karthikeyan; Hsu-Feng Lee; Hung-Pin Hsu; Yu-Cheng Shao; Yi-Ping Wang; Ching-Wei Tung (Chemical Engineering Journal, 2026)

A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

A digital-enabled circular recovery system for post-consumer inhalers: Linking material recovery, behaviour, and carbon reduction - Huong Thanh Hoang; Luong Cao Tung Son; Yu-Fen Huang; Ren-Hao Pan; Phuong Truc Nguyen Le; I-Chun Chuang; Huang-Chi Chen; Hung-Pin Tu; Chih-Hsing Hung; Da-Wei Wu (Journal of Cleaner Production, 2026)

Mapping climate-conditioned PM2.5 response under climate change in Taiwan using a high-resolution Geo-AI model - Pei-Yi Wong; Wei-Lun Hsu; Chieh-Ying Chen; Chien-Fei Chen; Chia-Wei Hsu; Shih-Chun Candice Lung; Ta-Chih Hsiao; Chia-Pin Yu; Wan-Yu Liu; Pau-Chung Chen; Wei Jie Seow; Chien-Hao Sung; et al. (Journal of Environmental Management, 2026)

Assessing the impact of climate variability on exposure indices of Portunid crabs in the Southern East China sea - Irene Chia Ling Lim; Yan-Lun Wu; Wei-Pin Hsu; Muhamad Naimullah; Wei-Yu Lee; Lu-Chi Chen; Kuo-Wei Lan (International Journal of Remote Sensing, 2026)

Diffusion of iodide in compacted Beishan Granite: Impact of saturation duration, ionic strength, and dry density - Yunpeng Yi; Jiayu Zhou; Hengtao Liu; Wujian Jin; Jingye She; Danwen Qin; Chuan-Pin Lee; Hanyu Wu; Mingliang Kang (Journal of Environmental Radioactivity, 2026)

Numerical analysis of the interaction mechanism between the dual-row jet hydraulic mining collector and deep-sea sediment - Pin-Jian Wang; Li Li; Jia-Bin Wu (Computers and Geotechnics, 2026)

Age-stratified genomic analyses reveal population-specific genetic determinants of exceptional longevity in Taiwan - Ming-Shun Hsieh; Shu-Min Yang; Shu-Hui Liao; Chayanika Goswami; Pei-Hsuan Wu; Tzu-Hung Hsiao; Yi-Ming Chen; Sung-Yuan Hu; Chorng-Kuang How; Tzu-Pin Lu; Amrita Chattopadhyay (GeroScience, 2026)

Projected impacts of climate change on the spatial distribution and habitat preference of tropical tuna in the Pacific Ocean - Yan-Lun Wu; Ting-Yu Liang; Wei-Pin Hsu; Teruhisa Shimada; Anindya Wirasatriya; Parichat Wetchayont; Chunhua Qiu; Kuo-Wei Lan (Marine Environmental Research, 2026)

Analysis of the failure mechanisms and treatment effectiveness of the Houlang village landslide - Ke Wu Liao; Qing Yu Zhang; Qing Lü; Pin Hong Gao (Bulletin of Engineering Geology and the Environment, 2026)

Botulinum neurotoxin A alleviates Deinagkistrodon acutus venom-induced limb injury through promoting macrophage polarization in rabbits - Lutao Xie; Haohao Wu; Linjie Lai; Wang Du; Jiefeng Xu; Pin Lan (Toxicon, 2026)

Purinergic ion channel-type P2X7 receptor regulates SK3 channel to promote the progression of gastric cancer - Pin Wan; Chang-bing Wu (Tissue and Cell, 2026)

Active site-rich MIL-101(Fe) derived P-doped iron sulfide/carbon octahedra for oxygen evolution electrocatalysis - Ying-Jun Jhang Jian; Pin-Yan Lee; Subbiramaniyan Kubendhiran; Lu-Yin Lin; Kevin C.-W. Wu; Kuo-Chuan Ho (Journal of Environmental Chemical Engineering, 2026)

Closed-loop recycling and recovery of vanadium cathodes from waste aqueous zinc-ion batteries - Hsing-Kai Tseng; Jun-An Su; I-Mao Chen; Yu-Ze Chen; Jun-Yi Wu; Pin-Han Chen; Fan-Wei Liu (Chemical Engineering Journal, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Insecticide resistance monitoring and identification of ryanodine receptor mutations driving diamide resistance in Cnaphalocrocis medinalis - Hong-Shuang Li; Pin-Xuan Lin; Meng-Zhen Wang; Bei-Bei Dong; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2026)

Soil Texture Controls Terrestrial Water Storage Anomalies in the Chinese Loess Plateau - Shuangyi Xu; Wende Zheng; Tianfeng Gu; Xi-Pin Wu; Kang-Jun Huang (CATENA, 2026)

Detection of Marteilioides chungmuensis in cultured Portuguese oyster (Crassostrea angulata) in southern Taiwan - I-wen Chen; Chieh-Hao Wu; Yi-Pin Lu; Yu-Ju Lin (Fish & Shellfish Immunology, 2025)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

An investigation of localized entropy driven cathode electrolyte interphase to a one-step complete deprotonation of ethylene carbonate on Ni-rich layered material of lithium-ion battery - Laurien Merinda; Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Chusnul Khotimah; Han-Pin Hsieh; Jeng-Kuei Chang; Shu-Chih Haw; Chih-Wen Pao; Jeng-Lung Chen; Qunjie Xu; et al. (Chemical Engineering Journal, 2025)

Dietary Supplementation with Multi-strain Probiotic Formulation (Bifidobacterium B8101, Lactobacillus L8603, Saccharomyces bayanus S9308, and Enterococcus SF9301), Betaine or their Combination Promotes Growth Performance Via Improving Intestinal Development in Broilers - Dan Hu; Xiaoting Wu; Pin Song; Manman Hou; Li’an Pan; Xiaoran Yang; Qinwei Sun; Yingdong Ni (Probiotics and Antimicrobial Proteins, 2025)

Novel insights into the effect of sTIM-3 on NLRP3 inflammasome via interacting with ASC - Xiaodi Zhang; Na Han; Ziqing Xu; Zheng Tong; Xiaolei Ren; Yang Sun; Chunyang Li; Xuetian Yue; Zhuanchang Wu; Xiaohong Liang; Chunhong Ma; Pin Wang; et al. (Inflammation Research, 2025)

A point-of-care testing biosensing platform integrated with physiologically based pharmacokinetic model for on-site therapeutic drug monitoring of methotrexate - Feng-Feng Zhang; Mei-Juan Wu; Zi-Wei Yu; Yi-Lan Lin; Pin-Fang Huang; Meng-Meng Liu (Chemical Engineering Journal, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Variations in the leaf economics spectrum, anatomical, ultrastructural, and stomatal traits of five tree species in the urban-rural air pollution environment - Xiangru Yan; Pin Li; Xianjie Wu; Jiahui Wang; Zejin Wang; Jingliang Xu; Xiaofan Hou; Dayong Fan; Zhengbing Yan; Enzai Du (Journal of Environmental Sciences, 2025)

Oncolytic avian reovirus regulates the TLR3-IRF3-IFN-γ-JAK-STAT1 and TLR3-NF-κB-IFN-γ-JAK-STAT1 pathways inducing autophagy in murine melanoma cells - Chao-Yu Hsu; Zi-Yang Lo; Yi-Ying Wu; Wei-Ru Huang; Tz-Chuen Ju; Kuo-Pin Chuang; Lon-Fye Lye; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Multi-hazard fragility analysis of cross-sea cable-stayed bridges cable bent tower under seismic-wind combined action - Yan Liang; Yu-zhen Kong; Li Yan; Zheng-hao Zhao; Pin-wu Guan (Soil Dynamics and Earthquake Engineering, 2025)

Performance Analysis of Poppet Valves in Deep-Sea Hydraulic Systems: Considering Viscosity–Pressure Characteristics - Pin-Jian Wang; Jia-Bin Wu (Journal of Marine Science and Engineering, 2025)
Deep-sea hydraulic systems, powering a wide range of numerous deep-sea operating equipment, employ many poppet valves to adjust the pressure and flow rate, thereby realizing precise movements of the actuators. With greater depths and ambient pressures, the hydraulic oil viscosity increases exponentially, leading to a significant difference in the performance of the poppet valve compared to on-land usage and across varying depths. Based on the shear stress transport (SST) k-ω turbulence model and the dynamic mesh method, a computational fluid dynamics (CFD) model of the poppet valve was established. With the viscosity–pressure characteristics considered, the performance of the poppet valve was analyzed under different depths, different inlet flow rates, and different cracking pressures. The results indicate significant performance deterioration in poppet valves at increased depths, characterized by increased pressure loss and extended response rise time. At 11 km underwater, the pressure loss can be 7 MPa larger than the preset cracking pressure of 10 MPa, and the rise time is doubled compared with the land condition. It is recommended to use hydraulic oils with a lower initial viscosity and a slower increase in viscosity with pressure in deep sea conditions.

Structure identification and biological activity of a novel sulfated glycosaminoglycan-like polysaccharide from Sepia recurvirostra ink - Nanqi Cheng; Na Gao; Pin Wang; Yujun Ma; Pengfei Li; Xiaolu Wu; Jiaying Sun; Yulan Dai; Jinhua Zhao (Carbohydrate Polymers, 2025)

Enhanced SERS performance through defect-guided growth of 2D/3D AuAg nanoplates for chemical sensing and cellular imaging applications - Kuan-Wen Liu; Pei-Yu Sie; Hsi-Ying Chen; Fong-I Ho; Po-Sheng Huang; Pin Chieh Wu; Mei-Yi Liao (Analytica Chimica Acta, 2025)

Geoarchaeological study of the evolution of rice farming fields in prehistoric Yangtze Delta and Huai River regions of China - Yijie Zhuang; Pin Ding; Lina Zhuang; Yonglei Wang; Wenwan Wu; Xia Wang; Yulong Niu; Guoping Sun; Xingtao Wei; Ling Qin (Quaternary Science Reviews, 2025)

Immune response to polystyrene microplastics: Regulation of inflammatory response via the ROS-driven NF-κB pathway in zebrafish (Danio rerio) - Jincheng Pei; Shannan Chen; Qingxia Ke; Anning Pang; Mengmeng Niu; Nan Li; Jiayi Li; Zhi Wang; Hongjuan Wu; Pin Nie (Aquatic Toxicology, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Fast screening of COVID-19 inpatient samples by integrating machine learning and label-free SERS methods - Jaya Sitjar; Huey-Pin Tsai; Han Lee; Chun-Wei Chang; Xin-Ni Wu; Jiunn-Der Liao (Analytica Chimica Acta, 2025)

Sacrificial reduction effects derived inorganic-rich hybrid solid electrolyte interfaces for long-term and high reversibility aqueous zinc-ion batteries - Yu Chen; Jiahong Fan; Qian Li; Pin Yi; Houfu Tu; Dedong Shan; Wentao Wang; Shulin Zhao; Yang Zhang; Yuping Wu; Yuhui Chen; Dengji Xiao (Chemical Engineering Journal, 2025)

Effects of forest bathing and the influence of exposure levels on cognitive health in the elderly: Evidence from a suburban forest recreation area - Jittakon Ramanpong; Chen Tsao; Jie Yin; Chih-Da Wu; Yu-Chih Huang; Chia-Pin Yu (Urban Forestry & Urban Greening, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Comparison of UV based advanced oxidation processes (UV/H2O2, UV/NaClO, and UV/Na2S2O8) for inactivating Uronema marinum in marine water - Xuan Chen; Pin Gan; Kunling Huang; Fangyu Liang; Tianhao Wu; Xudong Li; Yuanyuan Zhang (Journal of Water Process Engineering, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Air effects on solitary waves impinging and overtopping an impermeable seawall - Pin-Tzu Su; Kai-Cheng Hu; Tso-Ren Wu; Shih-Chun Hsiao (Ocean Engineering, 2024)

Research on the optimal pick-up heights and their control strategy for the hydraulic double-row jet collector of the manganese nodule miner - Pin-Jian Wang; Li Li; Dong-Chao Xie; Mi-Qian Fan; Jia-Bin Wu (Ocean Engineering, 2024)

The Effect of Platelet Fibrin Plasma (PFP) on Postoperative Refractory Wounds: Physiologically Concentrated Platelet Plasma in Wound Repair - Lu Fan; Ying Zhang; Xiankun Yin; Silu Chen; Pin Wu; Tianru Huyan; Ziyang Wang; Qun Ma; Hua Zhang; Wenhui Wang; Chunyan Gu; Lu Tie; et al. (Tissue Engineering and Regenerative Medicine, 2024)

Towards automatic urban tree inventory: Enhancing tree instance segmentation via moving object removal and a chord length-based DBH estimation approach - Wai Yi Chau; Jun Kang Chow; Tun Jian Tan; Jimmy WU; Mei Ling Leung; Pin Siang Tan; Siu Wai Chiu; Billy Chi Hang Hau; Hok Chuen Cheng; Yu-Hsing Wang (Computers and Electronics in Agriculture, 2024)

New insights into biofouling worsening induced by salinity stress in membrane bioreactor: Response of quorum sensing system and its regulation role - Weilong Song; Huaning Wu; Enyu Liu; Boyan Xu; Pin Zhao; Xinhua Wang; How Yong Ng (Chemical Engineering Journal, 2024)

Impact of polystyrene nanoplastics on apoptosis and inflammation in zebrafish larvae: Insights from reactive oxygen species perspective - Jincheng Pei; Shannan Chen; Li Li; Kailun Wang; Anning Pang; Mengmeng Niu; Xueyun Peng; Nan Li; Hongjuan Wu; Pin Nie (Science of The Total Environment, 2024)

Bisphenol M inhibits mouse oocyte maturation in vitro by disrupting cytoskeleton architecture and cell cycle processes - Huilei Chen; Yang Liu; Yue Huang; Pin Zhang; Danli Du; Wenhua Yu; Caiyun Wu; Hongzhen Ruan; Ping Zhou; Zhiming Ding; Huifen Xiang (Reproductive Toxicology, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Comparison of the inactivation of Uronema marinum in mariculture by UV/chlorine, UV/monochloramine, and UV/chlorine dioxide: Efficiency, mechanism and feasibility - Pin Gan; Xuan Chen; Yuanyuan Zhang; Xudong Li; Fangyu Liang; Tianhao Wu; Pengfei Xue; Kefu Yu (Journal of Water Process Engineering, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

Research on the Power Output of Different Floating Wind Farms Considering the Wake Effect - Jiaping Cui; Xianyou Wu; Pin Lyu; Tong Zhao; Quankun Li; Ruixian Ma; Yingming Liu (Journal of Marine Science and Engineering, 2024)
For floating wind turbines, one of the most interesting and challenging issues is that the movement of the rotor is strongly related to its floating platform, which results in corresponding variations in the wake characteristics of the turbine. Because the aerodynamic efficiency of the downstream turbines is affected by the wake characteristics, the power output will consequently vary depending on the different types of floating wind turbines and floating wind farms used. In this study, the rotor movement, wake characteristics, and corresponding wind farm power output are analyzed using a numerical method for three typical floating wind turbines: the semisubmersible type, spar buoy type, and tension leg platform type with a 5 MW configuration. A fixed-bottom monopile wind turbine is adopted as a benchmark. The simulation results show that of the three floating wind turbines, the rotor position and wake center are most dispersed in the case of the spar buoy type, and its wake also has the lowest impact on downstream wind turbines. Additionally, the power output of the corresponding spar buoy type wind farm is also the highest at different wind speeds, followed by the semisubmersible type, tension leg platform type, and then the fixed-bottom type. In particular, at low wind speeds, the wake effects differ significantly among the various types of wind turbines.

Nitrogen addition alleviates water loss of Moso bamboo (Phyllostachys edulis) under drought by affecting light-induced stomatal responses - Xi-pin Wu; Xiaomin Gao; Ruichang Zhang; Junwei Luan; Yi Wang; Shirong Liu (Science of The Total Environment, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

SIRT6 positively regulates antiviral response in a bony fish, the Chinese perch Siniperca chuatsi - Xiang Yang Wu; Zhi Wei Zhang; Shan Nan Chen; An Ning Pang; Xue Yun Peng; Nan Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2024)

Chlorpyrifos-induced suppression of the antioxidative defense system leads to cytotoxicity and genotoxicity in macrophages - Yin-Che Lu; Chen-Yu Chiang; Shih-Pin Chen; Yu-Wei Hsu; Wen-Ying Chen; Chun-Jung Chen; Yu-Hsiang Kuan; Sheng-Wen Wu (Environmental Toxicology and Pharmacology, 2024)

Co-pyrolysis of sewage sludge and phosphate tailings: Synergistically enhancing heavy metal immobilization and phosphorus availability - Ya Xiao; Tinggui Yan; Pin Yao; Weixue Xiang; Yunqi Wu; Jiang Li (Waste Management, 2024)

Mo, N co-doped cobalt hydroxide nanosheets for highly selective methanol-to-formate electrocatalytic conversion - Yaoxin Wu; Lili Ban; Hanzhen Wang; Qian Yang; Yaao Li; Ke Lu; Yuxiang Li; Pin Cui; Jinfeng Yang; Dalei Chang; Dezheng Yang; Feng Yu; et al. (Chemical Engineering Journal, 2024)

Anaerobic acidification membrane bioreactor operating at acidic condition for treating concentrated municipal wastewater: Performance and implication - Huihui Zhong; Qiming Wang; Mengfei Wu; Pin Zhao; Weilong Song; Xinhua Wang (Bioresource Technology, 2024)

Corrigendum to “Effects of blue space exposure in urban and natural environments on psychological and physiological responses: A within-subject experiment” [Urban For. Urban Green. 87 (2023) 1–9/128066] - Jie Yin; Jittakon Ramanpong; Jin Chang; Chih-Da Wu; Pei-Hua Chao; Chia-Pin Yu (Urban Forestry & Urban Greening, 2024)

Numerical study on the structural performances of the collector of the polymetallic nodule mining vehicle under different operating modes - Pin-Jian Wang; Li Li; Jia-Bin Wu (Ocean Engineering, 2024)

Numerical investigation of the hydrodynamic characteristics of the polymetallic nodule miner considering the internal fluid field - Pin-Jian Wang; Li Li; Jia-Bin Wu (Ocean Engineering, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Do greenness and landscape indices for greenspace correlate with suicide ratio? - Hsiao-Yun Lee; Hao-Ting Chang; Samuel Herianto; Chi-Shin Wu; Wan-Yu Liu; Chia-Pin Yu; Wen-Chi Pan; Chih-Da Wu (Landscape and Urban Planning, 2024)

Activation of peroxymonosulfate by sewage sludge-derived biochar to promote short-chain fatty acid production during sludge anaerobic fermentation - Jinling He; Qingchen Wu; Nan Jiang; Ai Zhang; Lin Wang; Xiang Li; Gang Xue; Hong Chen; Pin Gao (Chemical Engineering Journal, 2024)

Normal fault evolution in the Penghu Basin, a Paleogene Rift Basin in Western Taiwan Strait: A test of fault growth models - Pin-Rong Wu; Kenn-Ming Yang; Pin-Chi Wang; Chang-Jie Lee; Jong-Chang Wu (Tectonophysics, 2023)

Reverse genetic study reveals the molecular targets of chordotonal organ TRPV channel modulators - Yu-Xuan Peng; Zhao-Yu Liu; Pin-Xuan Lin; Shao-Cong Su; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2023)

Unveiling the fates of nitro-transformation products in advanced oxidation process: A DFT-based kinetic model - Pin Wang; Lingjun Bu; Lu Luo; Yangtao Wu; Weiqiu Zhang; Shiqing Zhou; John C. Crittenden (Chemical Engineering Journal, 2023)

AI-IoT integrated framework for tree tilt monitoring: A case study on tree failure in Hong Kong - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau (Agricultural and Forest Meteorology, 2023)

Effects of blue space exposure in urban and natural environments on psychological and physiological responses: A within-subject experiment - Jie Yin; Jittakon Ramanpong; Jin Chang; Chih-Da Wu; Pei-Hua Chao; Chia-Pin Yu (Urban Forestry & Urban Greening, 2023)

Source-apportionment and spatial distribution analysis of VOCs and their role in ozone formation using machine learning in central-west Taiwan - Manisha Mishra; Pin-Hsin Chen; Wilfredo Bisquera; Guan-Yu Lin; Thi-Cuc Le; Racha Dejchanchaiwong; Perapong Tekasakul; Ciao-Wei Jhang; Ci-Jhen Wu; Chuen-Jinn Tsai (Environmental Research, 2023)

Highly-specific aptamer targeting SARS-CoV-2 S1 protein screened on an automatic integrated microfluidic system for COVID-19 diagnosis - Hung-Bin Wu; Chih-Hung Wang; Yi-Da Chung; Yan-Shen Shan; Ying-Jun Lin; Huey-Pin Tsai; Gwo-Bin Lee (Analytica Chimica Acta, 2023)

Predicting the acoustic characteristics of seafloor sediments containing cold spring carbonate rocks - Yuhang Tian; Lei Wu; Dapeng Zou; Zhong Chen; Yongjun Jiang; Pin Yan; Chaoyan Fan (Frontiers in Marine Science, 2023)
The acoustic and physical properties of two valuable marine cold spring carbonate rock samples gathered from the Chaoshan Depression in the South China Sea were measured. The Wyllie time-average equation was applied to analyze the measured sound speeds and their trend under different porosities, and the sound speeds of marine cold spring carbonate rocks were found to be consistent with those of terrestrial carbonate rocks. The Voigt model, Reuss model, and Voigt-Reuss-Hill model were used to predict the characteristics of the sound speed for four states of seafloor sediments containing cold spring carbonate mineral particles or rocks. For these four states of marine cold spring carbonate mineral particles existing on or in seafloor sediments, the sound speed and reflection coefficient of a mixture of seafloor surface sediments containing cold spring carbonate mineral particles or rocks decrease with an increase in the volume ratio of the seafloor sediment. This method for predicting the reflection coefficient provides evidence to explain the high and low reflection coefficients observed in Chirp sub-bottom profiles of cold spring seepage areas.

Predictive models for the aqueous phase reactivity of inorganic radicals with organic micropollutants - Pin Wang; Lingjun Bu; Shiqing Zhou; Yangtao Wu; Lin Deng; Zhou Shi (Chemosphere, 2023)

Association between ambient air pollutant interaction with kidney function in a large Taiwanese population study - Wei-Yu Su; Da-Wei Wu; Hung-Pin Tu; Szu-Chia Chen; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2023)

Rational targeting of autophagy in colorectal cancer therapy: From molecular interactions to pharmacological compounds - Canhui Jin; Tianbao Wang; Yanhui Yang; Pin Zhou; Juncheng Li; Wenhao Wu; Xin Lv; Guoqing Ma; Aihong Wang (Environmental Research, 2023)

Regional comparison on ciguatoxicity, hemolytic activity, and toxin profile of the dinoflagellate Gambierdiscus from Kiribati and Malaysia - Jingyi Zhu; Wai Hin Lee; Ki Chun Yip; Zhen Wu; Jiajun Wu; Chui Pin Leaw; Po Teen Lim; Chung Kuang Lu; Leo Lai Chan (Science of The Total Environment, 2023)

Applications of convolutional neural networks for intelligent waste identification and recycling: A review - Ting-Wei Wu; Hua Zhang; Wei Peng; Fan Lü; Pin-Jing He (Resources, Conservation and Recycling, 2023)

Cytotoxic triterpenoids from the roots of Bupleurum scorzonerifolium - Dan-Qi Li; Zi-Wei Zhao; Fan Jiang; Da Liu; Xiao-Jing Wu; Xue-Gui Liu; Pin-Yi Gao (Phytochemistry Letters, 2023)

Nitrogen addition alleviates drought effects on water status and growth of Moso bamboo (Phllostachys edulis) - Xi-Pin Wu; Shirong Liu; Junwei Luan; Yi Wang; Xiaomin Gao; Chen Chen (Forest Ecology and Management, 2023)

Monitoring of tree tilt motion using lorawan-based wireless tree sensing system (IoTT) during super typhoon Mangkhut - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau; Kuan-Fu Liu; Billy Chi Hang Hau (Agricultural and Forest Meteorology, 2023)

Editorial: Coastal environmental and ecological data analysis - Meilin Wu; Yu-Pin Lin; Ana Carolina Ruiz-Fernández; Biraja Kumar Sahu (Frontiers in Marine Science, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Research on the lightweight structural optimization design of the front collector of the polymetallic nodule miner - Pin-Jian Wang; Li Li; Jia-Bin Wu (Ocean Engineering, 2023)

CDK1 promotes the proliferation of melanocytes in Rex rabbits - Yingying Dai; Shuaishuai Hu; Shaocheng Bai; Jiali Li; Naisu Yang; Pin Zhai; Bohao Zhao; Yang Chen; Xinsheng Wu (Genes & Genomics, 2022)

An Energy-Saving Position Control Strategy for Deep-Sea Valve-Controlled Hydraulic Cylinder Systems - Jia-Bin Wu; Li Li; Yong-Kang Yan; Pin-Jian Wang; Wei Wei (Journal of Marine Science and Engineering, 2022)
The valve-controlled hydraulic cylinder system (VCHCS) is commonly utilized in the underwater manipulator, which is the most important tool for subsea tasks. Hydraulic oil viscosity is very sensitive to pressure. Therefore, when working at different depths under different ambient pressures in the sea, the hydraulic oil viscosity and the pipeline pressure loss in the deep-sea VCHCS vary greatly, which seriously affects the energy efficiency of the system. In addition, the control accuracy of the deep-sea VCHCS is also influenced by changes in the hydraulic oil viscosity and the pipeline pressure loss. In order to realize energy-saving control, this research introduces a proportional relief valve and develops a variable pump pressure control strategy. At the same time, a variable gain proportional-integral-derivative (PID) algorithm is designed to achieve precise control. A co-simulation model of the deep-sea VCHCS is then established, and many simulation analyses are carried out. Compared with traditional PID control with a constant pump pressure, the proposed method presents advantages such as lower energy consumption, better control accuracy, better resistance to load impact, and accuracy consistency under different working depths. Among them, when working at 11 km depth in the sea, the proposed method is capable of saving energy by 36.5% for the multi-step movement, by 30% for the harmonic movement, and by 47% for the complex movement. The present work in this research provides a solution that can realize energy saving and precise control of the deep-sea VCHCS at the same time in the wide span of depth in the sea.

Working Performance of the Deep-Sea Valve-Controlled Hydraulic Cylinder System under Pressure-Dependent Viscosity Change and Hydrodynamic Effects - Jia-Bin Wu; Li Li; Xing-Long Zou; Pin-Jian Wang; Wei Wei (Journal of Marine Science and Engineering, 2022)
The valve-controlled hydraulic cylinder system (VCHCS) is commonly used for actuators such as manipulators in deep-sea equipment, whose working performance is crucial to subsea tasks. Affected by the ambient pressure introduced by the pressure compensator, the viscosity of the hydraulic oil increases significantly. On this basis, the viscosity changes further when flowing in the slender pipeline, making the pipeline pressure loss substantially increase and subsequently affecting the working performance of the deep-sea VCHCS. Aiming at this issue, a detailed nonlinear mathematical model of the deep-sea VCHCS is established, in which the viscosity-pressure characteristics of the hydraulic oil is considered to take the viscosity changes in the pipeline into account. Besides, the hydrodynamic effects are also included in the model. Then the corresponding numerical simulation model of the deep-sea VCHCS is established, and its working performance at different depths is simulated and analyzed. When the depth is 11km, the extension and retraction movements are delayed by 52.50% and 43.12% respectively. The root cause of the delay is then analyzed and discussed. Finally, the parameters that affect the working performance are studied, and suggestions to reduce or eliminate the delay phenomenon are given. The results can provide theoretical support for the performance optimization of the deep-sea VCHCS.

Effect of selected sampling media, flow rate, and time on the sampling efficiency of a liquid impinger packed with glass beads for the collection of airborne viruses - Yen-Chi Chen; I-Jen Wang; Chih-Ching Cheng; Yu-Chiao Wu; Chun-Hsuan Bai; Kuo-Pin Yu (Aerobiologia, 2021)

Deep convolutional neural network–based pixel-wise landslide inventory mapping - Zhaoyu Su; Jun Kang Chow; Pin Siang Tan; Jimmy Wu; Ying Kit Ho; Yu-Hsing Wang (Landslides, 2021)

Advances in intervention methods and brain protection mechanisms of in situ and remote ischemic postconditioning - Chun-Yan Li; Wei Ma; Kuang-Pin Liu; Jin-Wei Yang; Xian-Bin Wang; Zhen Wu; Tong Zhang; Jia-Wei Wang; Wei Liu; Jie Liu; Yu Liang; Xing-Kui Zhang; et al. (Metabolic Brain Disease, 2021)

Particulates and particulates-bound mercury (Hg(p)) sizes (PM18, PM10, PM2.5, PM1, PM<1) distributions study by using MOUDI sampler at a complex sampling site - Guor-Cheng Fang; Chao-Lang Kao; Pin-Wen Huang; Huang-Min Chen; Yu-Lun Wu; Gui-Ren Liang (Environmental Geochemistry and Health, 2020)

Correction to: Morphological Characterization and Gene Expression Patterns for Melanin Pigmentation in Rex Rabbit - Shuaishuai Hu; Pin Zhai; Yang Chen; Bohao Zhao; Naisu Yang; Manman Wang; Yeyi Xiao; Guolian Bao; Xinsheng Wu (Biochemical Genetics, 2019)

Morphological Characterization and Gene Expression Patterns for Melanin Pigmentation in Rex Rabbit - Shuaishuai Hu; Pin Zhai; Yang Chen; Bohao Zhao; Naisu Yang; Manman Wang; Yeyi Xiao; Guolian Bao; Xinsheng Wu (Biochemical Genetics, 2019)

Application of a stable carbon isotope for identifying Broussonetia papyrifera pollen - Chien-Cheng Jung; Chuan-Pin Lee; Wen-Chi Wang; Ming-Chee Wu; Huey-Jen Su (Environmental Science and Pollution Research, 2019)

Zircon trace elements and magma fertility: insights from porphyry (-skarn) Mo deposits in NE China - Qihai Shu; Zhaoshan Chang; Yong Lai; Xinlu Hu; Huaying Wu; Yong Zhang; Pin Wang; Degao Zhai; Cheng Zhang (Mineralium Deposita, 2019)

The validation of two major QTLs related to the timing of spring bud flush in Camellia sinensis - Li-Qiang Tan; Min Peng; Li-Yi Xu; Li-Yuan Wang; Kang Wei; Yao Zou; Sheng-Xiang Chen; Pin-Wu Li; Qian Tang; Hao Cheng (Euphytica, 2018)

Regulation of fine particulate matter (PM2.5) in the Pacific Rim: perspectives from the APRU Global Health Program - Chang-Fu Wu; Alistair Woodward; Ya-Ru Li; Haidong Kan; Rajasekhar Balasubramanian; Mohd Talib Latif; Mazrura Sahani; Tsun-Jen Cheng; Chia-Pin Chio; Nutta Taneepanichskul; Ho Kim; Chang-Chuan Chan; et al. (Air Quality, Atmosphere & Health, 2017)

Chemical characteristics of rainwater in karst rural areas, Guizhou Province, Southwest China - Pin Lü; Guilin Han; Qixin Wu (Acta Geochimica, 2017)

Comparison of two modified coal ash ferric-carbon micro-electrolysis ceramic media for pretreatment of tetracycline wastewater - Kunlun Yang; Yang Jin; Qinyan Yue; Pin Zhao; Yuan Gao; Suqing Wu; Baoyu Gao (Environmental Science and Pollution Research, 2017)

Determination of Dynamic Flexural Tensile Strength of Thermally Treated Laurentian Granite Using Semi-Circular Specimens - Tubing Yin; Pin Wang; Xibing Li; Bangbiao Wu; Ming Tao; Ronghua Shu (Rock Mechanics and Rock Engineering, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

Separation, determination and antifungal activity test of the products from a new Bacillus amyloliquefaciens - Tao Wang; Mian-Bin Wu; Zheng-Jie Chen; Jian-Pin Lin; Li-Rong Yang (Natural Product Research, 2016)

Molecular characterization and expression of ZAP-70 in Nile tilapia (Oreochromis niloticus) in response to Streptococcus agalactiae stimulus - Zhen Gan; Bei Wang; Wei Zhou; Yishan Lu; Yanfei Zhang; JiChang Jian; Zaohe Wu; Pin Nie (Genes & Genomics, 2016)

Population pharmacokinetics of vancomycin in adult Chinese patients with post-craniotomy meningitis and its application in individualised dosage regimens - Wei-wei Lin; Wei Wu; Zheng Jiao; Rong-fang Lin; Chang-zhen Jiang; Pin-fang Huang; Yi-wei Liu; Chang-lian Wang (European Journal of Clinical Pharmacology, 2016)

Highly stable rice-straw-derived charcoal in 3700-year-old ancient paddy soil: evidence for an effective pathway toward carbon sequestration - Mengxiong Wu; Min Yang; Xingguo Han; Ting Zhong; Yunfei Zheng; Pin Ding; Weixiang Wu (Environmental Science and Pollution Research, 2016)

Cerebral lipiodol embolism following abdomen trauma in a patient with hepatocellular carcinoma treated with transcatheter arterial chemoembolization - Quanmin Nie; Hao Wu; Pin Guo; Jianwei Ge; Yongming Qiu (Acta Neurologica Belgica, 2015)

Isolation and Characterization of an Erythromycin-Degrading Strain and Application for Bioaugmentation in a Biological Aerated Filter - Pin Gao; Xin Wei; Chaochao Gu; Xiaoqian Wu; Gang Xue; Weimin Shi; Weimin Sun (Water, Air, & Soil Pollution, 2015)

EGFR mediates docetaxel resistance in human castration-resistant prostate cancer through the Akt-dependent expression of ABCB1 (MDR1) - Tzyh-Chyuan Hour; Shiu-Dong Chung; Wang-Yi Kang; Ying-Chu Lin; Shu-Ju Chuang; A-Mei Huang; Wen-Jeng Wu; Shu-Pin Huang; Chao-Yuan Huang; Yeong-Shiau Pu (Archives of Toxicology, 2015)

Probabilistic framework for assessing the arsenic exposure risk from cooked fish consumption - Min-Pei Ling; Chiu-Hua Wu; Szu-Chieh Chen; Wei-Yu Chen; Chia-Pin Chio; Yi-Hsien Cheng; Chung-Min Liao (Environmental Geochemistry and Health, 2014)

Cadmium Neurotoxicity to a Freshwater Planarian - Jui-Pin Wu; Hui-Ling Lee; Mei-Hui Li (Archives of Environmental Contamination and Toxicology, 2014)

Application of AVO analysis to gas hydrates identification in the northern slope of the South China Sea - Rui Yang; Pin Yan; Nengyou Wu; Zhibin Sha; Jinqiang Liang (Acta Geophysica, 2014)

Oxidative Stress and Autophagic Alteration in Brainstem of SOD1-G93A Mouse Model of ALS - Ting An; Pengxiao Shi; Weisong Duan; Shipan Zhang; Pin Yuan; Zhongyao Li; Dongxia Wu; Zuoshang Xu; Chunyan Li; Yansu Guo (Molecular Neurobiology, 2014)

Influence of Cosubstrates on Iopromide Degradation by Pseudomonas sp. I-24 - Bingjie Xu; Pin Gao; Zhenhong Liu; Gang Xue; Yanan Liu; Fan Wu (Water, Air, & Soil Pollution, 2014)

A study of earthquake inter-occurrence times distribution models in Taiwan - Chi-Hsuan Chen; Jui-Pin Wang; Yih-Min Wu; Chung-Han Chan; Chien-Hsin Chang (Natural Hazards, 2013)

Associations of T helper 1, 2, 17 and regulatory T lymphocytes with mortality in severe sepsis - Huang-Pin Wu; Kong Chung; Chun-Yao Lin; Bor-Yiing Jiang; Duen-Yau Chuang; Yu-Chih Liu (Inflammation Research, 2013)

The integration of nautical hazard assessment and harbor GIS models to the Taichung Port area in Taiwan - Cheng-Wu Chen; Ching-Chung Lee; Chia-Hung Chen; Chun-Pin Tseng (Natural Hazards, 2013)

Application of GIS for the determination of hazard hotspots after direct transportation linkages between Taiwan and China - Cheng-Wu Chen; Ching-Chung Lee; Chun-Pin Tseng; Chia-Hung Chen (Natural Hazards, 2013)

A new viewpoint of hazard assessment and management for Taiwan’s insurance issues - Cheng-Wu Chen; Kevin Fong-Rey Liu; Meng-Lung Lin; Chun-Pin Tseng (Natural Hazards, 2013)

Hazard management and risk design by optimal statistical analysis - Cheng-Wu Chen; Kevin Fong-Rey Liu; Chun-Pin Tseng; Wen-Ko Hsu; Wei-Ling Chiang (Natural Hazards, 2012)

A novel strategy to determine the insurance and risk control plan for natural disaster risk management - Cheng-Wu Chen; Chun-Pin Tseng; Wen-Ko Hsu; Wei-Ling Chiang (Natural Hazards, 2012)

PGA distributions and seismic hazard evaluations in three cities in Taiwan - Jui-Pin Wang; Su-Chin Chang; Yih-Min Wu; Yun Xu (Natural Hazards, 2012)

Default risk-based probabilistic decision model for risk management and control - Cheng-Wu Chen; Chun-Pin Tseng (Natural Hazards, 2012)

Identification of Putative Artemisia annua ABCG Transporter Unigenes Related to Artemisinin Yield Following Expression Analysis in Different Plant Tissues and in Response to Methyl Jasmonate and Abscisic Acid Treatments - Ling Zhang; Xu Lu; Qian Shen; Yunfei Chen; Tao Wang; Fangyuan Zhang; Shaoyan Wu; Weimin Jiang; Pin Liu; Lida Zhang; Yueyue Wang; Kexuan Tang (Plant Molecular Biology Reporter, 2012)

Bioaccumulation and Toxicodynamics of Cadmium to Freshwater Planarian and the Protective Effect of N-Acetylcysteine - Jui-Pin Wu; Hon-Cheng Chen; Mei-Hui Li (Archives of Environmental Contamination and Toxicology, 2012)

Risk and uncertainty analysis in the planning stages of a risk decision-making process - Wen-Ko Hsu; Chun-Pin Tseng; Wei-Ling Chiang; Cheng-Wu Chen (Natural Hazards, 2012)

Natural disaster management mechanisms for probabilistic earthquake loss - Chun-Pin Tseng; Cheng-Wu Chen (Natural Hazards, 2012)

A new viewpoint on risk control decision models for natural disasters - Chun-Pin Tseng; Cheng-Wu Chen; Yu-Ping Tu (Natural Hazards, 2011)

Domain combination of the vertebrate-like TLR gene family: implications for their origin and evolution - BAOJUN WU; TIANXIAO HUAN; JING GONG; PIN ZHOU; ZENGLIANG BAI (Journal of Genetics, 2011)

The distribution of annual maximum earthquake magnitude around Taiwan and its application in the estimation of catastrophic earthquake recurrence probability - Jui-Pin Wang; Chung-Han Chan; Yih-Min Wu (Natural Hazards, 2011)

Association of hypomethylation of LINE-1 repetitive element in blood leukocyte DNA with an increased risk of hepatocellular carcinoma - Jian-zhong Di; Xiao-dong Han; Wen-ye Gu; Yu Wang; Qi Zheng; Pin Zhang; Hui-min Wu; Zhong-zheng Zhu (Journal of Zhejiang University-SCIENCE B, 2011)

Prazosin induces p53-mediated autophagic cell death in H9C2 cells - Yi-Fan Yang; Chau-Chung Wu; Wen-Pin Chen; Yuh-Lien Chen; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)

α-Mangostin Suppresses Phorbol 12-myristate 13-acetate-Induced MMP-2/MMP-9 Expressions via αvβ3 Integrin/FAK/ERK and NF-κB Signaling Pathway in Human Lung Adenocarcinoma A549 Cells - Yuan-Wei Shih; Shang-Tao Chien; Pin-Shern Chen; Jian-Hui Lee; Shu-Hau Wu; Li-Te Yin (Cell Biochemistry and Biophysics, 2010)

Transforming growth factor-β type I receptor/ALK5 contributes to doxazosin-induced apoptosis in H9C2 cells - Yi-Fan Yang; Chau-Chung Wu; Wen-Pin Chen; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

The taxonomy and phylogeny of the cyprinid genus Opsariichthys Bleeker (Teleostei: Cyprinidae) from Taiwan, with description of a new species - I-Shiung Chen; Jui-Hsien Wu; Shih-Pin Huang (Environmental Biology of Fishes, 2009)

Serial cytokine levels in patients with severe sepsis - Huang-Pin Wu; Chian-Kuang Chen; Kong Chung; Jo-Chi Tseng; Chung-Ching Hua; Yu-Chih Liu; Duen-Yau Chuang; Chung-Han Yang (Inflammation Research, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Assessing Impacts of Typhoons and the Chi-Chi Earthquake on Chenyulan Watershed Landscape Pattern in Central Taiwan Using Landscape Metrics - Yu-pin Lin; Tsun-kuo Chang; Chen-fa Wu; Te-chih Chiang; Shin-hwei Lin (Environmental Management, 2006)

Immunohistochemical Detection of Apoptotic Proteins, p53/Bax and JNK/FasL Cascade, in the Lung of Rats Exposed to Cigarette Smoke - Cheng-Hsun Wu; Hui-Hsuan Lin; Fu-Pin Yan; Cheng-Hua Wu; Chau-Jong Wang (Archives of Toxicology, 2006)

Contrasting phylogeographical patterns of two closely related species, Machilus thunbergii and Machilus kusanoi (Lauraceae), in Taiwan - Su‐Hwa Wu; Ching‐Yuan Hwang; Tsan‐Piao Lin; Jeng‐Der Chung; Yu‐Pin Cheng; Shih‐Ying Hwang (Journal of Biogeography, 2006)
Aim The purpose of this paper was to study the patterns of genetic variation, demographic history, haplotype relationships and potential location of diversity centres of two closely related species, Machilus thunbergii and Machilus kusanoi . Location The phylogeography of M. thunbergii and M. kusanoi was examined by sampling 110 and 106 individuals from 25 and 16 sampling sites, respectively, across their distributional range in Taiwan. Machilus thunbergii is distributed on the Asian mainland, South Korea, southern Japan, the Ryukyus, Taiwan and the Philippines, whereas M. kusanoi is endemic to Taiwan. These two species are closely related, and both are widely distributed in Taiwan but occupy different altitudinal zones and habitats. Methods The range‐wide variation of M. thunbergii and M. kusanoi in Taiwan was studied using chloroplast DNA (cpDNA) variations. A haplotype network was constructed with the computer program tcs . Nested clade analysis was conducted with the computer program ceodis , and various parameters of genetic diversity were calculated and neutrality tested by the computer program D na SP. Population differentiation was estimated using the programs arlequin and hapstep . The contribution of the populations to gene diversity and to allelic richness was calculated using the software contrib . The level of divergence for each population from the remaining populations was calculated as the mean value of pairwise F ST for each population against the rest of the populations. Results Extremely low levels of genetic differentiation were found for both species. This result suggested that these two species probably survived in multiple relict refugia with different population sizes throughout the island during low‐temperature periods of the Pleistocene. In addition, nested clade analysis (NCA) of cpDNA haplotypes indicated that restricted gene flow with isolation‐by‐distance characterized the recolonization after the Pleistocene by Tashueshan and Shiouhluan populations of M. thunbergii in the north‐central area west of the Central Mountain Range (CMR). In contrast, NCA analysis indicated that a major diversity centre on the southern tip of the island (Kending population) and contiguous range expansion characterized the recolonization by M. kusanoi of northern areas along the east side of the CMR. The major diversity centres found for the two species examined were further supported by the results of the mean F ST for individual populations in comparison with other populations, and of the contribution of the divergence component to the total diversity. Main conclusions This research supports the multiple relict refugia hypothesis for both species investigated. Populations of M. thunbergii at Shiouhluan and Tashueshan in the north‐central area west of the CMR represent a diversity centre currently expanding its size. A diversity centre at the southern‐edge population of M. kusanoi , and a contiguous range expansion from Kending, were found. These results indicate that the M. thunbergii populations at Tashueshan and Shiouhluan and the M. kusanoi population at Kending, and even Soukar, are evolutionarily significant units for conservation programmes.

A crossover study on lipid and weight changes associated with olanzapine and risperidone - Kuan-Pin Su; Po-Lun Wu; Carmine M. Pariante (Psychopharmacology, 2005)

Density-dependent natural selection in Drosophila: Adaptation to adult crowding - Amitabh Joshi; Wan-PIN Wu; Laurence D. Mueller (Evolutionary Ecology, 1998)